1978
DOI: 10.1121/1.381810
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination by young infants of voiced stop consonants with and without release bursts

Abstract: Infant discrimination of synthetic voiced stop consonants, contrasting in place of articulation, was investigated using the high-amplitude sucking paradigm. Discrimination of [d•z]--[ga] contrasts, with and without release bursts, was compared. The results provide some evidence that the presence of a burst facilitates place discrimination by infants, perhaps by enchancing integrated spectral properties characteristic of the individual stop consonants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Our failure then to observe any differences in discrimination performance for the two types of stimuli suggests that infants are not any more sensitive to global, invariant properties of the CV syllable onset spectrum than they are to local details of the waveform, such as formant transition information or even quite small spectral differences. This result suggests that Williams and Bush's (1978) conclusion concerning infants' superior discrimination of five-formant + burst stops relative to stops without bursts may have been inaccurate-particularly in light of the interpretative problems associated with their study as we noted earlier.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Our failure then to observe any differences in discrimination performance for the two types of stimuli suggests that infants are not any more sensitive to global, invariant properties of the CV syllable onset spectrum than they are to local details of the waveform, such as formant transition information or even quite small spectral differences. This result suggests that Williams and Bush's (1978) conclusion concerning infants' superior discrimination of five-formant + burst stops relative to stops without bursts may have been inaccurate-particularly in light of the interpretative problems associated with their study as we noted earlier.…”
Section: Discussionmentioning
confidence: 54%
“…Moreover, no conclusions about the relative discriminability of onset spectra and formant transition cues can be made on the basis of this work. A study by Williams and Bush (1978) is suggestive in this respect. With the high-amplitude sucking paradigm, these investigators studied infants' discrimination of synthetic /da/-/ga/ contrasts in which the stimuli either did or did not contain release bursts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jerger's (Jerger, Jerger, & Lewis, 1981) work is an exception; she, too, found children's speech perception to be closely related to receptive vocabulary age. Greater attention has been given to developmental effects associated with voicing-onset-time (VOT) and temporal characteristics of the stimuli (Krause, 1978;Simon & Fourcin, 1978;Tallal, 1981;Williams & Bush, 1978;Zlatin & Koenigsknecht, 1975). Developmental perceptual changes have also been demonstrated for synthetic voiced-stop consonants differing in place of articulation (Elliott, Longinotti, Meyer, Raz, & Zucker, 1981).…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Some of these studies suggest that development of vowel and consonant perception is largely complete in the first few years of childhood -around 5 to 6 years of age, with some aspects refining till the adolescent years; while some studies have reported less than ceiling scores even for children as old as 10 to 12 years. 14,17,19 For normal development of speech perception and production in the early years and for appropriate and typical use of verbal communication through life, the hearing sense needs to be intact.…”
Section: Introductionmentioning
confidence: 99%